POLA PENGEMBANGAN KEWIRAUSAHAAN PETANI PENGRAJIN GULA KELAPA KRISTAL - Sulistyani Budiningsih; Watemin Watemin (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2014)
Research aim to: 1) Analyzing factors causing farmer of worker of coconut sugar will alter the product of coconut sugar print to become the product of crystal sugar in Countryside Rancamaya of Subdistrict Cilongok 2) Analyzing condition entrepreneur of farmer of worker of crystal sugar in Countryside Rancamaya of Subdistrict Cilongok 3) Compiling pattern of development entrepreneur farmer of worker of crystal sugar in Countryside of Rancamaya of Subdistrict Cilongok. Research method conducted by survey. Research location in Countryside Rancamaya specified in intend the (purposive sampling. Result of analysis show some factor of cause of worker farmer ready the produce of crystal sugar 1) willingness of Farmer of entrepreneur of crystal sugar 2) Owning specialty 3) Effort crystal sugar more beneficial 4) Price sell the higher crystal sugar product 5) System of product marketing easy crystal sugar 6) price of product of crystal sugar relative stabilize, and 7) There are of awareness of worker farmer follow the training. condition of entrepreneur of worker of crystal sugar in Countryside Rancamaya that is 1) Sum up the ownership of coconut tree pertained to by lower horizontally the ownership of 29 tree of farmer 2) Capital stem from person and borrow the wholesaler 3) Workers of most responder formally lower 4) Inclusive of productive age faction horizontally flatten the responder experience 2-3 year 5) Flatten to the production of crystal sugar reach 4,69 per day and product packaging still modestly and 6) Price sell the higher crystal sugar product. Pattern of Development of entrepreneurship of worker of crystal sugar conducted by maximizing potency or strength owned to utilize to reach for the opportunity in an optimal fashion that is the existence of experience and spirit of entrepreneur of worker farmer supported by local potency resources as strength in realizing product diversification of crystal sugar. Make-up of organizational group of farmer of worker of crystal sugar so that to be can run the better management function again of construction continue from government, related institution and LSM. Make-up of quality of resources of human being utilize to improve the management produce in an optimal fashion and continue utilize to fulfill the domestic market request and abroad. Make-up of quality of raw material of modern nira adjusment of technology and utilize to reach the quality of good crystal sugar product as one of effort product. Key words: farmer of coconut sugar, crystal sugar